Implementasi Digital Storytelling sebagai Inovasi Pembelajaran Sejarah dalam Menstimulasi Kemampuan Interpretasi dan Analisis Kritis - Ragil Pangestu; Muhammad Zalva Zakira; Herni Mandala Putri; Syarifuddin Syarifuddin; Rani Oktapiani (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2026)
History education at the secondary level continues to face challenges in fostering higher order thinking skills, particularly students’ interpretative and critical analytical abilities, which are often constrained by textual and chronological instructional approaches. This study aims to conceptually examine the role of digital storytelling as a pedagogical strategy to strengthen historical interpretation and critical analysis within the frameworks of constructivism, historical thinking, and critical thinking theory. The research employs a qualitative approach based on literature review, utilizing descriptive and thematic analysis of scholarly works and educational policy documents. The findings indicate that digital storytelling promotes active cognitive engagement through processes of source selection, credibility evaluation, evidence based narrative construction, and multiperspective reflection. The production of digital narratives functions not merely as a creative activity but as a cognitive mechanism that trains logical argumentation and validation of historical evidence. Furthermore, the integration of multimedia elements enhances contextual understanding and deepens students’ meaning making of historical events. Nevertheless, its implementation encounters challenges related to teachers’ digital competence, students’ digital literacy readiness, infrastructural limitations, and instructional time allocation. The study implies that digital storytelling holds strategic potential as a pedagogical approach to develop historical thinking competencies in the digital era, provided that it is supported by systematic instructional planning and sustained capacity building in educational institutions.